VIDEO REPEATER DESIGN CONCEPT FOR UAV CONTROL (Computer systems and information technologies, 2024)
This study is aimed at the utilization of a video repeater for unmanned aerial vehicle (UAV) control, involving a comparative analysis of existing scientific literature, methodologies, and available solutions. Through comparative analysis, the method of using an external repeater emerged as the most promising, offering flexibility in selecting repeaters with superior performance and advanced capabilities. Notably, this approach allows for the utilization of a single repeater across multiple UAVs and facilitates convenient modification or upgrade of the repeater without necessitating alterations to the UAV itself.Following component selection, an experimental prototype was designed to facilitate empirical investigations. Additionally, a frequency transmission scheme was devised for quadcopter control employing the repeater.This research contributes to advancing UAV control systems by introducing a novel approach to video repeater integration, poised to enhance operational efficiency and adaptability in diverse settings. The findings from this study are anticipated to inform further developments in UAV technology, particularly in optimizing video transmission for improved situational awareness and mission effectiveness.
Keywords: unmanned aerial vehicles; video repeater